On Female Subjectivity and Power: Gender Politics and Occupational Sex Segregation in The Conductor - Hung-Chang Liao; Ya-Huei Wang (Journal of Language and Literature, 2025)
Research has shown that gender inequality persists at managerial levels, with an increasing number of women occupying middle and lower managerial positions while men dominate higher managerial roles. This phenomenon, often referred to as the “glass ceiling,” represents an invisible barrier characterized by gender biases that prevent women from attaining high-level positions within organizations. A notable gender gap remains in the professionalization of the classical music field, particularly in orchestral conducting. To understand how gender politics and occupational sex segregation affect women’s career development, workplace relationships, and gender relations, this study conducts qualitative research using latent-content analysis of the film The Conductor. It examines how women experience occupational sex segregation under gender politics and societal norms. The findings reveal that deep-rooted gender norms and biases within male-dominated professions not only limit women’s access to leadership roles but also reinforce occupational segregation. By highlighting the struggles of women in breaking barriers, the studyexplores the potential for women to cultivate their own female subjectivity, empowering them to overcome occupational sex segregation and affirming their significance in male-dominated professions. This research has some limitations as it focuses on the narratives of an individual female in the film and hence cannot adequately represent the diverse experiences of women in different occupations. Future research may compare and analyze real-life cases from different occupations and cultural backgrounds to gain a comprehensive understanding of gender dynamics.